Positive psychology in the working environment. Job demands-resources theory, work engagement and burnout: A systematic literature review - Galanakis, Michael D.; Tsitouri, Elli (Frontiers in Psychology, 2022)
The purpose of the present systematic review is to examine the Job Demands-Resources (JD-R) model in order to pinpoint how applicable and relevant is the present theoretical framework in the 21st Century workplace environment. Initially, there will be an examination of the key concepts of the theory, followed by a brief investigation of the empirical validity and importance of the theory in the workplace environment. Then, there will be an empirical investigation of various studies of both cross-sectional and longitudinal nature in the form of a methodology, offering substantial empirical evidence that attests to the validity and effectiveness of the JD-R model in predicting work engagement and burnout-two independent and contrasting states of employee wellbeing, covering the entire spectrum from employee wellness to employee ill-health. We hope this review contributes to the advancement of the JD-R model, aiding researchers and practitioners to obtain a better understanding of the current state of the JD-R model, whilst also offering avenues for future development of the theory, ultimately resulting in a better prediction of employee wellbeing.